NUTRITIONAL ANALYSIS OF CHICKEN LIVER AND MORINGA LEAVES MEATBALLS: SOURCE OF IRON FOR ADOLESCENT GIRLS - Tenrirawe, A. Nurul Maulida; Indriasari, Rahayu; Hidayanty, Healthy; Sirajuddin, Saifuddin; Mansur, Marini Amaliah (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2022)
ABSTRACT Introduction: One of the causes of anemia is a lack of iron intake due to increased iron needs in adolescence. The combination of heme and non-heme foodstuffs is expected to optimize iron absorption in the body, such as chicken liver and moringa leaves. Aim: This research aims to find out the best formula picture, the content of macro and micro meatballs based on chicken liver and moringa leaves as an alternative food source of iron for young women. Methods:The design of this study is descriptively laboratory-based. In this study, nutritional analysis was conducted on the best formula selected from five formulas that have been tested organoleptic, namely formula IV. The results of the nutritional analysis obtained were compared with beef meatballs and looked at the contribution of these products to the adequacy of AKG in adolescents girl. Results: The results showed that the nutritional content of the formula was selected in one serving (180 grams) which is 42.25 g of carbohydrates, 1.44 g of fat, 11.65 g of protein, 6.53 mg of iron, 12.89 μg of vitamin A and 68.45 mg of vitamin C. The nutritional content can meet the adequacy of adolescents girls in the age range of 13-15 years carbohydrates range 14.08%, fat range 17.92%, protein range 2.06%, iron range 43.60%, vitamin A range2.15%, vitamin C range 105.31%, and energy range11.15%. The product can sufficient nutritional needs adequacy for adolescents girls at the age of 15-18 years. Carbohydrates, proteins, fats, iron, vitamin A are the same as before, vitamin C is range 91.27%, and energy range 10.88%. Conclusion: The nutritional content of chicken liver-based meatballs and moringa leaves can be an option to meet the needs of iron and other important nutrients for adolescents girls. Keywords : Chicken liver, Moringas Leaves, Meatballs, Anemia, Nutritional Content